TEACHING READING THROUGH RECIPROCAL TEACHING METHOD - Beny Hamdani (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2020)
This paper aims to investigate whether the university students who are taught reading through Reciprocal Teaching Method achieve better in reading ability than those who are taught through Direct Reading Thinking Activities. The design of this study is a quasi-experimental, non-randomized control group, pretest-posttest since it is conducted in a classroom setting that the subjects have been organized into classes. The subject of the study was the fourth term of university students of English education study program consisting 30 university students. The instrument of this research was a test as Pre-test and Post-test in the form of reading comprehension questions. The data analysis used Independent T-Test. Based on the result of the calculation of post-test from experimental and control groups, the alternative hypothesis (Ha) was accepted. The result of the study shows that the use of the Reciprocal Teaching Method can improve the university students’ reading ability. It proves the hypothesis of the study that students who are taught reading through the Reciprocal Teaching method achieve better in reading ability than those who are taught through Direct Reading Thinking Activities. Based on this result, it can be concluded that the Reciprocal Teaching Method can be used as an alternative method to teach reading, so that the students are able to understand the texts comprehensively. It also makes the university students more active in the teaching learning process and can improve their ability as well.